‘Ekaterina’ - a new spring wheat variety - N. N. Zezin; V. A. Vorobiev; A. V. Vorobiev (Зерновое хозяйство России)
Due to a great change of climatic conditions in the Sverdlov region in the last decades, wheat breeding deals mainly with the development of middle early varieties. The assessment of breeding material is carried out on the crop rotation fields, which belong to the principal share of lands in the Sverdlov region and Perm Area. The breeding resulted in the growing of a new middle early variety ‘Ekaterina’ by the method of intraspecific hybridization between an early maturing mother form ‘Iren’ and a middle maturing variety ‘Krasnoufimskaya 100’. Since 2013 the variety ‘Ekaterina’ has been in the State Varity Testing, since 2015 in the State Register of breeding achievements in Volga-Vyatka and West-Siberia regions. The average productivity of the variety in the competitive trial (2009-2014) was 4.5 t/ha that exceeded the standard (‘Gornouralskaya’) on 0.57 t/ha. Under favourable humidity the maximum productivity of the variety was 6.87 t/ha or on 1.13 t/ha more than of the standard variety. ‘Ekaterina’ is more advantageous than ‘Gornouralskaya’ in such traits as ‘1000-seed weight’, productivity of a head, protein amount per hectare and its energetic value, energetic efficiency of cultivation, gross increase of productivity a day per hectare during the periods ‘sprouting-wax maturity’ and ‘earing-wax maturity’, parameters of adaptive ability (general adaptive ability and breeding value of a genotype). In the Krasnoufimsk Breeding Center ‘Ekaterina’ exceeded the varieties ‘Gornouralskaya’. ‘Iren’, ‘Irgina’, ‘Novosibirskaya 15’ and ‘Svecha’ on 0.33-1.08 t/ha on the variety test plots of the Sverdlov region and Perm Area. In 2014 during the trial in SPK “Kolkhoz named after Sverdlov” (the Sverdlov region) a new variety produced 3.30 t/ha on 60 ha and exceeded the variety ‘Simbirtsit’ on 0.36 t/ha (12.2%). In OOO “Agrofirma Manchazhskaya” (14 ha) the variety exceeded ‘Iren’ on 0.40 t/ha (25.0%). In the same year in KFK “Pchela” (the Tyumen region) ‘Ekaterina’ produced 4.40 t/ha (on 10 ha), that exceeded ‘Iren’ on 0.30 t/ha (7.3%). The variety is practically stable to loose smut and it is more stable to root rot than the standard variety. Due to the general baking assessment the variety ‘Ekaterina’ slightly gives way to the variety ‘Gornouralskaya’.